Iodocuprate-containing ionic liquids as promoters for green propulsion. Issue 45 (1st November 2018) - Wang, Kangcai; Chinnam, Ajay Kumar; Petrutik, Natan; Komarala, Eswaravara Prasadarao; Zhang, Qinghua; Yan, Qi-Long; Dobrovetsky, Roman; Gozin, Michael
Abstract : New iodocuprate-containing ionic liquids with high thermostability were designed, prepared and evaluated as hypergolic reaction promoters between an energetic ionic fuel and a H2 O2 "green" oxidizer. Abstract : In this work, we prepared and comprehensively characterized four novel iodocuprate-containing ionic liquids, CuILs1–4 . In addition to their interesting molecular structures and physical properties CuILs exhibited capability to efficiently promote hypergolic reactions between boron-containing [EMIM + ][H3 BCN − ] and [MIM]·[BH3 ] fuels and a highly concentrated H2 O2 (95%) oxidizer. The most promising promoter CuIL3 has the decomposition temperature well above the decomposition temperature of the fuels, was stable in promoter-in-fuel mixtures for weeks and showed ignition delay times down to 14 ms. We believe that further development of our new iodocuprate ionic liquids can lead to promising "green" H2 O2 -based bipropellant systems for space applications.